2019
DOI: 10.1186/s12880-019-0354-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurements versus invasive intracranial pressure measurement method in patients with brain injury: a retrospective study

Abstract: Background The invasive method for intracranial pressure measurement is ‘gold standard’ but not always feasible because the intraventricular catheter/ intraparenchymal micro transducer used in the measurement of intracranial pressure measurement may cause complications. Imaging modalities with clinical examination protocol have a lack of specificity and accuracy. The objective of the study was to compare the accuracy of diagnostic parameters of ultrasound measurements in patients with brain injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
0
18
2
Order By: Relevance
“…Researchers have repeatedly reported the difficulties of performing prospective randomized clinical trials to evaluate the effect of ICP monitoring on outcomes of PICU patients, since there are ethical concerns of not monitoring ICP in the control group of patients. Major pediatric TBI guidelines are currently based on ICP measurements, while ICP monitoring has been established as a standard of care for sTBI [ 30 , 37 , 38 ]. Moreover, studies show that the implementation of evidence-based TBI treatment algorithms are associated with improved outcomes, highlighting the importance of future precise ICP-based guidelines in order to reduce practice disparity among TBI patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have repeatedly reported the difficulties of performing prospective randomized clinical trials to evaluate the effect of ICP monitoring on outcomes of PICU patients, since there are ethical concerns of not monitoring ICP in the control group of patients. Major pediatric TBI guidelines are currently based on ICP measurements, while ICP monitoring has been established as a standard of care for sTBI [ 30 , 37 , 38 ]. Moreover, studies show that the implementation of evidence-based TBI treatment algorithms are associated with improved outcomes, highlighting the importance of future precise ICP-based guidelines in order to reduce practice disparity among TBI patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jahns et al [2019] (16) found that patients with severe head injury receiving intracranial pressure monitoring and intensive care can reduce the fatality rate by more than 12%. In addition, the implementation of intracranial pressure monitoring can early detect changes in intracranial disease, determines cerebral perfusion pressure and cerebral blood flow, guides clinical treatment, and determines the prognosis of patients early and treat them early (17).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio ONSD/ETD takes into consideration anatomical differences among patients, the value above 0.25 is suggestive of intracranial hypertension. Optic nerve sheath diameter measurement is simple, non-invasive, safe, fast, and inexpensive [23]. Sepsis-associated brain dysfunction (SABD) is a common organ insufficiency in septic patients.…”
Section: Discussionmentioning
confidence: 99%